2014
DOI: 10.1097/01.asw.0000444849.71374.bc
|View full text |Cite
|
Sign up to set email alerts
|

Silver from Polyurethane Dressing Is Delivered by Gradient to Exudate, Tissue, and Serum of Patients Undergoing Negative-Pressure Wound Treatment

Abstract: The high concentration of silver found in wound exudate reflects not only the affinity for silver in serum components and wound fluids, but also that most silver ions are not distributed systemically in the patient; instead, they are transported by the vacuum created by therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…This means that silver ions are released and then absorbed by the dressing, and that silver is not lost during the vacuum therapy and can exert its antimicrobial effect on the wound bed without increasing its systemic toxicity. These results are consistent with data from other authors supporting the hypothesis that silver stays on the wound bed; moreover, its antimicrobial effect might even be enhanced by the acid environment caused by the vacuum …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This means that silver ions are released and then absorbed by the dressing, and that silver is not lost during the vacuum therapy and can exert its antimicrobial effect on the wound bed without increasing its systemic toxicity. These results are consistent with data from other authors supporting the hypothesis that silver stays on the wound bed; moreover, its antimicrobial effect might even be enhanced by the acid environment caused by the vacuum …”
Section: Discussionsupporting
confidence: 93%
“…These results are consistent with data from other authors supporting the hypothesis that silver stays on the wound bed; moreover, its antimicrobial effect might even be enhanced by the acid environment caused by the vacuum. 11,21,22 Nanocrystalline silver (Acticoat) in patients with burns has been shown to be safe, with maximum silver levels in serum of 56.8 mg L 21 after a median time of 9 days, which were not associated with hematologic or biochemical toxicity. 23 Besides transient changes in the metabolism of certain enzymes, severe liver damage or advanced argyria have not been reported, even with blood silver levels in blood >200 mg L 21 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is reported that such a dressing is not effective in delivering silver ions to the wound and most silver is removed by the suction force and found in the wound exudate. 27 In case of using WED, the wound maintains a direct contact with the dressing and receives the benefit of continuous microcurrent generated by WED. Recent work in our laboratory shows that WED disrupts Pseudomonas aeruginosa PAO1 biofilm by a redox-sensitive pathway.…”
Section: Discussionmentioning
confidence: 99%